(untitled) (Research, Society and Development, 2021)
The work investigated a possible reconciliation between indigenous culture in a process of inculturation during christian-protestant proselytism. By identifying the main principles to be observed by the Sateré-Mawé Indians in their culture, through a field research in the villages near the Maués city, it was possible to establish the level of adaptation that they experienced, when migrating their way of life to the christianity. The methodology applied was that of descriptive research presenting the results obtained in a qualitative approach. These methodologies made it possible to record data analysis, through the application of questionnaires and interviews carried out on the spot. The results of the analyzes will be used to point out a new form of evangelization for these peoples in general. The cycle of planning, execution, verification and action was established through the cause and effect diagram “Ishikawa”, which facilitated the observation, data collection and analysis of the information obtained, so that a new action model could be proposed.